Descrizione e spiegazione di ‘visibili’ grammaticalizzazioni attestate nella diacronia del cinese: tra linguistica storica e linguistica cognitiva (Atti del Sodalizio Glottologico Milanese, 2019)
Description and explanation of ‘visible’ grammaticalization processes in the Chinese language diachrony: between historical and cognitive linguistics. The paper, according to historical- and cognitive linguistic points of view, deals with some processes of grammaticalization of a few Indo-European Languages compared withanalogous processes attested in Chinese. As far as concerns Indo-European Languages, historical comparative criteria are adopted; as regards Chinese, particular attention is given to the relationship between the phono-morphological level of some morphemes and their codification in the written language. The historical development of four Chinese morphemes are specifically analyzed: bǎ 把 (Verb ‘to take’/preposition), shēng 生 (Verb ‘to be naturally’/derivational morpheme), yòng 用 (Verb ‘to use’/instrumental/comitative preposition), liǎo/le了 (Verb ‘to end’ > ‘to complete (a cognitive process)’ > ‘to understand’/postposition/particle). KEYWORDS: Grammaticalization processes of Indo-European languages, grammaticalization processes of Chinese language, relationship between morphemes and semantic values, relationship between morphemes and written codification